THE PROBLEMS OF ACCOUNTING AND TAXATION IN PAWNSHOPS - NINA Golysheva (Учёт. Анализ. Аудит)
The article features the peculiarities of accounting of income and expenses as well as taxation methods in pawnshops. The article studies the normative regulations of pawnshops, as well as the specifics and features of their business activities. The various situations of collateral loans, timely repayments of due debts, repayments of the overdue debts and non-return debts are carefully analyzed in the article. The features of statutory regulations and accounting in case of foreclosure are described in the article. The article analyzes the purpose and the description of a strict reporting form - “pawn ticket” as the main recording medium, which is drawn up in pawnshops.The article outlines the historical background of the origins and development of pawnshop business and particular attention is paid to the prospects and the problems in accounting for this type of business.